CSS in JavaScript - Schau, Dustin (Manning Publications, 2019)
"CSS in JavaScript: With styled-components and React introduces you to developing modern applications that include CSS written directly in your JavaScript files, rather than as separate stylesheets. Taking on something this new can be daunting, but expert instructor Dustin Schau brings his wealth of experience on CSS in JS with lessons that will let you digest what you learn easily. After starting with a brief introduction to CSS in JS and what it actually means, you'll quickly start using React and the library styled-components to build your first styled component. You'll see how to inject props, grapple with inheritance, and get to grips with all sorts of pseudo styles, media queries, and cool animations. Then, with real-world exercises you can bring to your own work, you'll focus on extending your creations with advanced features like server-side rendering, theming support, and even a brief segue into CSS modules and automated tooling. Top everything off with a look at when not to use CSS in JS, and you'll be ready to use the skills and techniques you've picked up right away!"--Resource description page